Characterization of the m6A-Associated Tumor Immune Microenvironment in Prostate Cancer to Aid Immunotherapy - Liu, Zezhen; Zhong, Jiehui; Zeng, Jie; Duan, Xiaolu; Lu, Jianming; Sun, Xinyuan; Liu, Qinwei; Liang, Yingke; Lin, Zhuoyuan; Zhong, Weide; Wu, Wenzheng; Cai, Chao; et al. (Frontiers in Immunology, 2021)
The aim of this study was to elucidate the correlation between m6A modification and the tumor immune microenvironment (TIME) in prostate cancer (PCa) and to identify the m6A modification patterns suitable for immune checkpoint inhibitors (ICIs) therapy. We evaluated the m6A modification patterns of PCa based on 24 m6A regulators and correlated these modification patterns with TIME characteristics. Three distinct m6A modification patterns were determined in PCa. The m6A cluster with the best prognosis had significantly increased METTL14 and ZC3H13 expression and was characterized by low mutation rate, tumor heterogeneity, and neoantigens. The m6A cluster with a poor prognosis had markedly high KIAA1429 and HNRNPA2B1 expression and was characterized by high intratumor heterogeneity and Th2 cell infiltration, while low Th17 cell infiltration and Macrophages M1/M2. The m6Ascore was constructed to quantify the m6A modification pattern of individual PCa patients based on m6A-associated genes. We found that the low-m6Ascore group with poor prognosis had a higher immunotherapeutic response rate than the high-m6Ascore group. The low-m6Ascore group was more likely to benefit from ICIs therapy. This study was determined that immunotherapy is more effective in low-m6Ascore PCa patients with poor prognosis.